2017
DOI: 10.1111/asj.12766
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enzymatically treated Artemisia annua L. on growth performance and some blood parameters of broilers exposed to heat stress

Abstract: To evaluate the effects of enzymatically treated Artemisia annua L. (EA) on growth performance and some blood parameters of broilers exposed to heat stress (HS), 320 22-day-old Arbor Acres male broilers were randomly allotted into five groups with eight replicates of eight birds each. Broilers in the control group were housed at 22 ± 1°C and fed the basal diet. Broilers in the HS, HS-EA , HS-EA and HS-EA groups were reared under HS (34 ± 1°C for 8 h/day and 22 ± 1°C for 16 h/day), and fed basal diet with 0, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 43 publications
(74 reference statements)
4
26
0
Order By: Relevance
“…Similarly, Wan et al. () reported broilers subjected to 21 days cyclic heat stress had significantly increased the rectal temperature at 42‐day‐old. Bernabucci et al.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Similarly, Wan et al. () reported broilers subjected to 21 days cyclic heat stress had significantly increased the rectal temperature at 42‐day‐old. Bernabucci et al.…”
Section: Discussionmentioning
confidence: 82%
“…Abnormal activities of ALP, ALT, AST, and LDH in serum are also indicators of tissue damage, particularly in liver and muscle (Nyblom, Berggren, Balldin, & Olsson, ; Xue et al., ). Some studies reported that serum ALT and AST activities were increased under heat stress (Hosseini‐Vashan, Golian, & Yaghobfar, ; Wan et al., ). Recently, Luo et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations